The Advance and Critical Functions of Energetic Carbon Dots in Carbon Dioxide Photo/Electroreduction Reactions. Issue 12 (26th October 2022) - Bao, Kaili; Shi, Jie; Liao, Fan; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract: As a unique carbon‐based nano material, carbon dots (CDs) have attracted great attention because of their special structures and properties, and have been widely used in various fields, such as bio‐imaging technology, catalyst design, pollutant degradation, chemical analysis, clean energy development and so on. CDs are used as catalysts or cocatalysts for multiple energy conversion reactions due to their advantages of valid visible light utilization, fast transmission of charge carriers, excellent catalytic activity, and good electrical conductivity. This review first summarizes the basic structure and properties of CDs. The advance and critical functions of energetic CDs in carbon dioxide photo/electroreduction reactions are discussed in detail. Due to the excellent optical absorption, electron transfer properties and good conductivity of CDs, they can enhance catalytic activity and stability effectively. In the end, the existing problems and future development opportunities of CDs‐based catalysts in CO2 reduction reaction are proposed and outlined. Abstract : As a unique carbon based nanomaterial, carbon dots (CDs) have been widely used in the field of catalytic CO2 reduction reactions due to their unique physical and chemical properties. Based on this, this review introduces the basic structures and properties of CDs, and discusses the key role of CDs in CO2 photo/electroreduction reactions.